Upaya Pencegahan Tindak Pidana Korupsi di Kantor Badan Pengelola Keuangan dan Aset Daerah di Kabupaten Lampung Utara - Tasya Balqis Uftimentari; Raden Qushay Affaishal; Fajar Ammar Ikhsanuddin Al Aslami (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
Corruption is a serious issue that can hinder development and undermine good governance. This article discusses various anti-corruption prevention efforts implemented at the Office of the Regional Financial and Asset Management Agency (BPKAD) in Kotabumi, North Lampung. This study uses a descriptive qualitative approach, with data collected through interviews, observations, and document analysis. The findings indicate that BPKAD has adopted several preventive strategies, including increased transparency in budget management, the implementation of internal control systems, and ethics and integrity training for employees. Additionally, the use of information technology has been utilized to minimize the potential for irregularities. The main challenges in these efforts include resistance to change and a lack of awareness among some officials about the importance of anti-corruption culture. Therefore, stronger commitment from all organizational elements and support from external parties are needed to create a clean and accountable work environment.